Radon survey in Chelyabinsk Oblast, Russia, in 2008–2011. Analysis of spatial variability of indoor radon concentration - A. M. Marennyy; D. V. Kononenko; A. E. Trufanova (Радиационная гигиена)
An extensive radon survey was conducted in 2008-2011 in the framework of the Federal target program on the territory of 29 districts of Chelyabinsk Oblast. SSNTDs were used to measure indoor radon concentrations in public buildings, dwellings and industrial buildings. The results are stored in the database “Radon” owned by Research and Technical Center of Radiation-Chemical Safety and Hygiene of Federal Medical-Biological Agency. The paper presents the results of the analysis of spatial variability of indoor radon concentration and the relationship of this value with a set of geological predictors of radon potential of the territory integrated into a map of ecological and radiogeochemical zones. The results show that in all districts and the whole Chelyabinsk Oblast radon concentrations conform to a lognormal distribution, but in ten districts log-logistic distribution fits the data slightly better. Nevertheless, relative difference between the median values of indoor radon concentration calculated from the two fitted distributions yields zero. The results show that dose assessment based on the arithmetic means could lead to an overestimation of the doses from radon in 1.4 times on average compared to that based on the medians. The median value does not exceed 400 Bq/m3 in any of the surveyed territories and the 95th percentile lies between 96 and 1274 Bq/m3. The fraction of indoor radon concentrations above 400 Bq/m3 expected from the fitted distribution lies between less than 0.1 and 26.8%. The highest values of this fraction were obtained for the Sosnovsky, Kaslinsky, Bredinsky districts and the Miassky urban district (except for the city of Miass). A map of ecological and radiogeochemical zones in Chelyabinsk Oblast was released in 1993-1995 and it was based on a set of geological predictors of radon potential of the territory. We analyzed the relationship of these zones with the results of the radon survey. One-way ANOVA on ranks with the Bonferroni correction showed that there is no statistically significant difference at the 95% confidence level amongst the medians of indoor radon concentration on basement, ground and first floors in settlements, which are located on the territory of three of four of these zones and outside of the territory of all zones. In the fourth zone the median was even two times lower than outside of the zones. These results lead to the conclusion that the possibility of using this map as a map of radon-prone areas is very doubtful. Each datapoint stored in the “Radon” database has a number of additional properties, which allows analyzing other types of indoor radon concentration variability such as seasonal or floor-to-floor. It is expected that later this dataset could be used for estimating regional seasonal correction factors.